2005
DOI: 10.1038/sj.npp.1300946
|View full text |Cite
|
Sign up to set email alerts
|

Role for Dopamine Neurons of the Rostral Linear Nucleus and Periaqueductal Gray in the Rewarding and Sensitizing Properties of Heroin

Abstract: There is a mesencephalic dopaminergic network outside the ventral tegmental area (VTA), including structures such as the rostral linear nucleus (RLi) and periaqueductal gray (PAG). These nuclei project to neural areas implicated in reinforcing effects of drugs, indicating that they could participate in opiate reward. The objectives were to study the morphological characteristics of the dopamine network of the RLi/PAG region, and to discern its role on rewarding and sensitizing effects of heroin in rats, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 55 publications
0
45
0
1
Order By: Relevance
“…We recently have shown that the VGLUT2 protein is present in THexpressing DA nerve terminals within these target regions, thereby verifying the ability of the DA neurons to use glutamate as a cotransmitter (32). The RLi recently was shown to be involved in mediating the rewarding effects of heroin (33). The presence of VGLUT2, specifically in mDA neuronal populations important for mediating rewarding effects of drugs of abuse, suggests a functional role of VGLUT2-mediated neurotransmission in drug-induced mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…We recently have shown that the VGLUT2 protein is present in THexpressing DA nerve terminals within these target regions, thereby verifying the ability of the DA neurons to use glutamate as a cotransmitter (32). The RLi recently was shown to be involved in mediating the rewarding effects of heroin (33). The presence of VGLUT2, specifically in mDA neuronal populations important for mediating rewarding effects of drugs of abuse, suggests a functional role of VGLUT2-mediated neurotransmission in drug-induced mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies suggest that dopaminergic (e.g. [8,20,33,35]) and glutamatergic (e.g. [17,27,30]) systems may also mediate opiate-induced reward or locomotor activity.…”
Section: Discussionmentioning
confidence: 99%
“…The ventral PAG is not a part of the main columns of the PAG studied in the present review (i.e., the dorsomedial, dorsolateral, lateral and ventrolateral columns) and, in addition to the A10dc, contains other important monoaminergic cell groups (i.e., the dorsal raphe nucleus). In contrast to other parts of the PAG, the A10dc does not seem to influence anxiety-like responses and basal locomotion but has been implicated in drug seeking and reward, including conditioned place preference to heroin, heroin-induced reward and methamphetamine seeking (Flores et al, 2006;Sobieraj et al, 2016).…”
Section: Pag and Seeking Behaviormentioning
confidence: 99%